LC‐MS/MS analysis of Gegen Qinlian Decoction and its pharmacokinetics after oral administration to rats. (18th August 2014) - Zhang, Yifan; Yuan, Jin; Zhang, Yizhu; Chen, Ye; Cao, Jiaoxian; An, Rui; Wang, Xinhong
Abstract: A liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method was developed and validated for the simultaneous determination of 12 constituents of Gegen Qinlian Decoction (GQD), namely puerarin, daidzein, baicalin, wogonoside, wogonin, liquiritin, liquiritigenin, berberine, jatrorrhizine, palmatine, coptisine and glycyrrhetic acid, in rat plasma. The plasma samples were spiked with the internal standard (IS) carbamazepine acidified with HCl and extracted by liquid–liquid extraction with ethyl acetate. Chromatographic separation was achieved on a Shiseido Capcell PAK C18 column utilizing a gradient elution profile and a mobile phase consisting of (A) 0.1% formic acid in water and (B) acetonitrile. Detection was performed in the multiple reaction monitoring mode using electrospray ionization in the positive ion mode at a flow rate of 0.3 mL/min and a run time of 8 min. All of the calibration curves gave good linearity ( r > 0.9930) over the concentration range from 0.6–360 to 16.2–9720 ng/mL for all components. The intra‐ and inter‐day precisions were <15.0% in terms of the relative standard deviation, and the accuracies were within ±13.7% in terms of the relative error. The method was successfully applied to investigate the pharmacokinetics of the major active compounds of Gegen Qinlian Decoction after its oral administration to rats. Copyright © 2014 John Wiley & Sons, Ltd.